Effect of Type of Grain and Oil Supplement on the Performance, Blood Lipoproteins, Egg Cholesterol and Fatty Acids of Laying Hens - Shafey, T.M.; Dingle, J.G.; McDonald, M.W.; Kostner, K. (International Journal of Poultry Science, 2003)
The effects of type of grain (wheat vs. sorghum) and oil supplement/kg diet [0, 20g olive oil (OL), 20g safflower oil (SO), 10 g OL plus 10 g SO (OLSO)], over a 12-week period on the performance, plasma and lipoproteins lipids [cholesterol (C), triglycerides (TG), phospholipid (P)], and yolk C and fatty acids concentrations of laying hens were studied. Hens fed on the sorghum diet had significantly (P<0.05) higher yolk oleic acid concentration and oleic:linoleic acid ratio and plasma TG concentration in the low density plus high density lipoproteins (LDL plus HDL) fraction when compared with hens fed on the wheat diet. Birds fed on the OL diet had significantly (P<0.05) higher yolk oleic acid concentration and oleic:linoleic acid ratio, and plasma TG concentration in the VLDL fraction and lower plasma TG concentration in the LDL plus HDL fraction (P<0.01) when compared with those fed on the control diet. Hens fed on the SO diet had significantly (P<0.05) higher concentration of yolk linoleic acid and plasma lipids in the very low density lipoproteins (VLDL) fraction and lower yolk oleic:linoleic acid ratio and plasma TG concentration in the LDL plus HDL fraction (P<0.01) than hens fed on the control diet. Whilst, birds fed on the OLSO diet produced significantly (P<0.05) higher yolk unsaturated:saturated fatty acids ratio and lower palmitic and stearic acids concentrations when compared with those fed on the control diet. Dietary treatments did not significantly affect the weight gain, feed intake, rate of lay, egg and yolk weights, yolk lipid and C concentrations, daily C output, plasma total lipid concentration, plasma C and P concentrations in the LDL plus HDL fraction of hens. It was concluded that hens fed a sorghum based diet or a diet supplemented with olive oil produced eggs with high concentration of oleic and oleic:linoleic acid ratio and that hens fed a diet supplemented with safflower oil produced eggs with high concentration of linoleic and lower oleic:linoleic acid ratio and that hens fed a diet supplemented with olive plus safflower oils produced eggs with high concentration of unsaturated:saturated fatty acid ratio and lower palmitic and stearic acids.